Vascular niche promotes hematopoietic multipotent progenitor formation from pluripotent stem cells - Gori, Jennifer L. (J Clin Invest, 2015)
Pluripotent stem cells (PSCs) represent an alternative hematopoietic stem cell (HSC) source for treating hematopoietic disease. The limited engraftment of human PSC–derived (hPSC-derived) multipotent progenitor cells (MPP) has hampered the clinical application of these cells and suggests that MPP require additional cues for definitive hematopoiesis. We hypothesized that the presence of a vascular niche that produces Notch ligands jagged-1 (JAG1) and delta-like ligand-4 (DLL4) drives definitive hematopoiesis. We differentiated hes2 human embryonic stem cells (hESC) and Macaca nemestrina–induced PSC (iPSC) line-7 with cytokines in the presence or absence of endothelial cells (ECs) that express JAG1 and DLL4. Cells cocultured with ECs generated substantially more CD34(+)CD45(+) hematopoietic progenitors compared with cells cocultured without ECs or with ECs lacking JAG1 or DLL4. EC-induced cells exhibited Notch activation and expressed HSC-specific Notch targets RUNX1 and GATA2. EC-induced PSC-MPP engrafted at a markedly higher level in NOD/SCID/IL-2 receptor γ chain–null (NSG) mice compared with cytokine-induced cells, and low-dose chemotherapy-based selection further increased engraftment. Long-term engraftment and the myeloid-to-lymphoid ratio achieved with vascular niche induction were similar to levels achieved for cord blood–derived MPP and up to 20-fold higher than those achieved with hPSC-derived MPP engraftment. Our findings indicate that endothelial Notch ligands promote PSC-definitive hematopoiesis and production of long-term engrafting CD34(+) cells, suggesting these ligands are critical for HSC emergence.